Acanthocybium solandri (Actinopterygii, Scombriformes, Scombridae) first record from Malta with notes on using its parasites as biological tags - Alan Deidun; Maria Corsini-Foka; Alessio Marrone; Gianni Insacco; Jean Paul Schembri; Arnold Sciberras; Mario Santoro; Flavia Occhibove; Antonio Di Natale; Bruno Zava (Acta Ichthyologica et Piscatoria)
The wahoo, Acanthocybium solandri (Cuvier, 1832), an uncommon scombrid species for the Mediterranean, is hereby reported for the first time from Maltese waters. Details of this unusual capture, and characteristics of the specimens recovered are provided, as well as a brief discussion on dynamics of its introduction in the Mediterranean Sea, and its distribution in this area. In addition, two individuals of the parasitic nematode Anisakis pegreffii Campana-Rouget et Biocca, 1955 (Anisakidae) were found from the stomach of one of the specimens.